Maternal High Fat Diet and Diabetes Disrupts Transcriptomic Pathways That Regulate Cardiac Metabolism and Cell Fate in Newborn Rat Hearts - Preston, Claudia C.; Larsen, Tricia D.; Eclov, Julie A.; Louwagie, Eli J.; Gandy, Tyler C. T.; Faustino, Randolph S.; Baack, Michelle L. (Frontiers in Endocrinology, 2020)
Background: Children born to diabetic or obese mothers have a higher risk of heart disease at birth and later in life. Using chromatin immunoprecipitation sequencing, we previously demonstrated that late-gestation diabetes, maternal high fat (HF) diet, and the combination causes distinct fuel-mediated epigenetic reprogramming of rat cardiac tissue during fetal cardiogenesis. The objective of the present study was to investigate the overall transcriptional signature of newborn offspring exposed to maternal diabetes and maternal H diet. Methods: Microarray gene expression profiling of hearts from diabetes exposed, HF diet exposed, and combination exposed newborn rats was compared to controls. Functional annotation, pathway and network analysis of differentially expressed genes were performed in combination exposed and control newborn rat hearts. Further downstream metabolic assessments included measurement of total and phosphorylated AKT2 and GSK3β, as well as quantification of glycolytic capacity by extracellular flux analysis and glycogen staining. Results: Transcriptional analysis identified significant fuel-mediated changes in offspring cardiac gene expression. Specifically, functional pathways analysis identified two key signaling cascades that were functionally prioritized in combination exposed offspring hearts: (1) downregulation of fibroblast growth factor (FGF) activated PI3K/AKT pathway and (2) upregulation of peroxisome proliferator-activated receptor gamma coactivator alpha (PGC1α) mitochondrial biogenesis signaling. Functional metabolic and histochemical assays supported these transcriptome changes, corroborating diabetes- and diet-induced cardiac transcriptome remodeling and cardiac metabolism in offspring. Conclusion: This study provides the first data accounting for the compounding effects of maternal hyperglycemia and hyperlipidemia on the developmental cardiac transcriptome, and elucidates nuanced and novel features of maternal diabetes and diet on regulation of heart health.